The Power of Visual Literacy: Affirmation Comics to Build English Motivation in Senior High Students - Reyandri, Dezla Borja; Aunurrahman, Aunurrahman; Putra, Muhammad Iqbal Ripo (Journal of Languages and Language Teaching, 2025)
This study aims to analyze the implementation of affirmation comics in fostering students’ motivation in English language learning. Using a classroom action research (CAR) design, the study followed four stages: planning, action, observation, and reflection. A total of 15 students participated in two cycles of intervention. Data were collected through observations and questionnaires, which included both closed-ended and open-ended items, and analyzed using descriptive statistics and thematic analysis. The results showed an increase in students’ learning motivation, particularly in terms of self-efficacy and appreciation for English learning. The classroom atmosphere shifted from being negative and unfocused in Cycle 1 to more positive and collaborative in Cycle 2. Students responded positively to the visuals and emotional messages in the comics, although challenges remained in comprehending the vocabulary. Unlike previous studies that primarily used comics to enhance linguistic skills, this study highlights the novelty of affirmation comics as a motivational tool that directly addresses students’ psychological and affective needs. This indicates that affirmation comics function not only as visual aids but also as affective scaffolds to reduce anxiety, strengthen self-efficacy, and build a positive classroom climate. Practically, teachers can integrate short, linguistically accessible affirmation comics with guided reflections or collaborative tasks to sustain students’ motivation and engagement in English learning.